Efficacy of Platelet-Rich Plasma in the Treatment of Equine Tendon and Ligament Injuries: A Systematic Review of Clinical and Experimental Studies - Jorge U. Carmona; Catalina López (Veterinary Sciences)
(1) Background: Tendon and ligament injuries are a leading cause of lameness in horses, with significant economic implications. Platelet-rich plasma (PRP) has gained attention for its regenerative potential, but its efficacy remains uncertain due to inconsistent study designs and reporting. (2) Methods: This systematic review, following the PRISMA guidelines, evaluated 22 studies (clinical and experimental) to assess the safety and efficacy of PRP in treating equine tendon and ligament injuries. The risk of bias was analyzed using the ROBINS-I and RoB 2.0 tools. (3) Results: PRP demonstrated a favorable safety profile, with no severe adverse effects reported. Clinical outcomes included improved lameness scores, ultrasonographic tissue organization, and return-to-work rates. However, variability in PRP formulations (e.g., leukocyte-rich vs. leukocyte-reduced) and activation methods (e.g., calcium chloride, thrombin) contributed to inconsistent results. Experimental studies supported PRP’s role in collagen synthesis and neovascularization, but comparative trials with stem cells or other therapies (e.g., extracorporeal shockwave) showed mixed results. The methodological quality of studies varied, with only 27% achieving “good” scores for PRP reporting. (4) Conclusions: PRP is a safe and potentially effective treatment, but its clinical application is hindered by a lack of standardization. Future research should focus on large, randomized controlled trials with uniform PRP protocols, long-term (≥2 years) efficacy assessments, comparative studies with MSC combinations, and cost-effectiveness analyses.